Introduction of Laboratory Endodontics: Evaluating the Perception of the Undergraduate Clinical Dental Students at a Nigerian University - Shakeerah Gbadebo; Amidu Sulaiman; Deborah Mojirade Ajayi (Nigerian Dental Association, 2023)
Background: Root canal treatment (RCT) forms a  part of the requirements for graduation for dental students. The students are expected to perform the procedure during their clinical training. However, most students are presented to the clinic without formal laboratory practical training. Aim: To introduce laboratory endodontic training and evaluate the perception of Nigerian undergraduate clinical dental students about the program. Methodology: A two-day hands-on training on RCT was done for a set of final-year dental students in the operative technique laboratory of the Department of Restorative Dentistry of the Institution. The training included taking the participants through all the steps involved in RCT. The participants performed all the stages of RCT on extracted lower molar teeth mounted on a phantom head with paraffin wax. Each student performed the two methods of biomechanical preparation taught: manual and rotary instrumentation, and later evaluated the training in terms of confidence and preparation for clinical exposure. Result:  Twenty-one (53.9%) students within the age range of 23 to 30 years and a  mean age of 25.4±1.7years completed the program. The majority, (81%) of the participants claimed the hands-on demonstration was very helpful in performing the procedure, and all submitted it will help their confidence during clinical exposure to RCT. The participants further suggested the incorporation of training into the regular school program. Conclusion:  The laboratory endodontic hands-on training was accepted by all the participants, and it was opined that it will boost their confidence in performing the procedure in the clinic.